A Review on Artificial Intelligence(AI), Big Data and Block Chain : Future Impact and Business Opportunities (Global Journal of Management and Business Research, 2020)
Mega trends are global, sustained, and macroeconomic forces of development that impacts business, economy, society, cultures and personal lives thus defines our future life. For different industries technological megatrends have different impacts. The way we have seen the technological development over last 10 years there is no doubt within 2030, technology is the sector which will have profound global impact in all kind of business entities. Financial sectors is already using the most of these technological megatrends and other sectors such as logistics, education, health care are also implementing these. The paper consists of three trend reflections where I have chosen three technological megatrends-Artificial Intelligence, Big Data and Block Chain for the analysis of their future impact on businesses and how the businesses can create greater value by the implementation of these technologies.
Keywords: technological megatrends; artificial intelligence (AI); blockchain; big data